Surface modification of natural leather using RF plasma discharge - Nagia Dawood (Journal of Taibah University for Science)
Radiofrequency (RF) low-pressure plasma has been applied to improve natural leather's wettability and water absorption. The plasma was generated using RF discharge of the Ar-He gas mixture at 60 and 120 W power using different treatment times (30, 60, 120, 180, and 300s). Before and after treatment, the contact angle, surface free energy, and water absorption ratio were measured. It was observed that a 300s plasma treatment time and plasma power 60 and 120 W is enough to decrease the water contact angle from 83.56 for an untreated sample to 0°. The surface-free energy and the water absorption ratio increase with an increase in the treatment time and plasma power. The findings demonstrate that plasma treatment increases the wettability of the surface of leather samples. In addition, the change in leather properties was analyzed by scanning electron microscopy, X-ray diffraction, and differential scanning calorimetry, Fourier transform infrared spectroscopy.